An interactive learning environment in Geographical Information Systems - Sarah Cornelius; Ian Heywood (Association for Learning Technology, 1998)
Geographical Information Systems (GIS) are computer-based tools for the input, management, analysis, modelling and display of geographical data. GIS are applied in a wide range of organizations and disciplines, including central and local government, environmental agencies, transport planning and vehicle navigation, education and research, utilities management, resource management, and the financial and retail sectors. GIS is a field of constantly changing technology, and it has been recognized that GIS education needs to be more than a 'once in a lifetime' event (Muller, 1993). Consequently, GIS teachers have developed computer-based materials for learners at all levels, from school students to postgraduates, and for the independent professional updating their skills and knowledge. To date, these materials have followed a number of approaches. Initially demonstrations of GIS software and its capabilities addressed the need to increase awareness of GIS and its applications (DoE, 1987). Arcdemo (Green, 1987) was an innovative early example, providing a demonstration of the software package Arc/Info online. Training in particular software, and the need for hands-on experience, have been addressed with the production of software-specific educational materials which use primarily traditional text-based instructions for exercises with specially prepared data. Examples include Getting started in GIS (Langford, 1993), the Unitar workbooks for Idrisi (for example McKendry et al, 1992) and Understanding GIS: the Arc/Info Method (ESRI, 1990). These have proved particularly popular, and by directing learners through structured exercises allow new users to become familiar with complex software in a relatively short time. More recently, they have migrated to CD-ROM, with training materials such as Getting to know Arcview (ESRI, 1995) provided in this format, and combining software, data and demonstrations.